Dietary Salt Intake and Gastric Cancer Risk: A Systematic Review and Meta-Analysis - Wu, Bo; Yang, Dehua; Yang, Shuhan; Zhang, Guangzhe (Frontiers in Nutrition, 2021)
The results of prospective cohort studies regarding the role of salt intake and subsequent gastric cancer risk are inconsistent. Thus, we performed a systematic review and meta-analysis to summarize the strength of the association of salt intake with gastric cancer morbidity and mortality. PubMed, EmBase, and Cochrane Library were systematically searched to identify eligible studies published throughout September 2021. The effect estimates with 95% confidence intervals (CIs) for gastric cancer morbidity or mortality in each study were applied to calculate the pooled results; these analyses were performed using the random-effects model. Twenty-six prospective cohort studies involving 4,956,350 individuals were selected; these studies reported 19,301 cases of gastric cancer and 2,871 cases of gastric cancer-associated mortality. High (RR: 1.25; 95%CI: 1.10-1.41; P=0.001) or moderate (RR: 1.20; 95%CI: 1.04-1.38; P=0.012) salt intake was associated with a greater risk of gastric cancer. High pickled food intake was associated with an increased gastric cancer risk (RR: 1.28; 95%CI: 1.05-1.57; P=0.017), while moderate pickled foods intake had no significant effect on gastric cancer risk (RR: 1.10; 95%CI: 0.88-1.37; P=0.390). Neither high (RR: 1.14; 95%CI: 0.95-1.36; P=0.161) nor moderate (RR: 1.10; 95%CI: 0.87-1.40; P=0.436) salted fish intake were associated with gastric cancer risk. A high intake of processed meat was significantly associated with a higher risk of gastric cancer (RR: 1.24; 95%CI: 1.03-1.49; P=0.023), while moderate processed meat intake had no significant effect on the gastric cancer risk (RR: 1.01; 95%CI: 0.92-1.11; P=0.844). High (RR: 1.04; 95%CI: 0.90-1.19; P=0.626) and moderate (RR: 1.02; 95%CI: 0.94-1.11; P=0.594) miso-soup intake had no effects on the gastric cancer risk. High intakes of salt, pickled food, and processed meat are associated with significantly increased risks of gastric cancer; these increased risks are also seen when participants consumed moderate amounts of salt.